THE FUNCTIONAL POSITION IN THE INDONESIAN NATIONAL POLICE - Setyawan, Nugroho Ari; Purnomo, Joko Agung; Pranata, Andi Yudha; Prasetyo, Dedy (Jurnal Ilmu Kepolisian, 2024)
This paper describes the implementation of functional position conception by the INP. The literature discussing the concept in specific and near terms is investigated. The functional position is widely discussed in the Indonesian literature. However, the direct term (the functional position) is hardly found in Western literature. The near term is the professional. The term discussion is associated with changing from a hierarchical to a flat and agile organisation. The flat and agile structure facilitates the work of cross-functional project teams (CFTs) and professionals. Moreover, the flat and agile structure means fewer managers, enlarging the professionals' roles. However, the police of some countries have not yet streamlined their structures to flat and agile organisations (including the Indonesian National Police [INP]).  This study is conducted through a literature review and document analysis. The global literature is reviewed narratively to explore the functional position concept. Subsequently, the functional position application in the INP is studied from the act, regulations and other documents.  The INP has developed various functional positions within the organisation since the inception of the Police Act 2002. Besides, the INP develops supporting elements for functional positions. The INP's units, officers, and CFTs may be more capable of handling policing problems by applying for the functional position initiative.   This study introduces the concept of the functional position of the INP to the global literature. The concept may be studied further to understand its mechanism and effectiveness in improving policing.